THE EFFECT OF COMPETENCY, WORK MOTIVATION, WORK DISCIPLINE AND ORGANIZATIONAL COMMITMENTS ON TEACHER PERFORMANCE - Fajar Supanto; Yosefna Almesdirta Kara; Muhammad Rizki Firdaus (Universitas Negeri Malang, 2021)
Abstract: This study aimed to describe the variables of competence, work motivation, work discipline, organizational commitment and teacher performance. In addition, analyzed the effect of competency variables, work motivation, work discipline, organizational commitment simultaneously affects teacher performance. The population were 100 respondents from Bina Sari Maumere Catholic Foundation teachers and the sample taken were 80 respondents. Furthermore, analysis of linear were used as a technique of analysis. The results showed that competency, work motivation, work discipline and organizational commitment simultaneously affected teacher performance. Similarly, those variables partially influenced teacher performance and Competence had a dominant effect on teacher performance at the Bina Sari Maumere Catholic Foundation as conclusion competence has a dominant effect on teacher performance. Keywords: Competency; Work Motivation; Work Discipline; Organizational Commitment and Teacher Performance